2018
DOI: 10.6063/motricidade.16239
|View full text |Cite
|
Sign up to set email alerts
|

Associação dos genótipos da ACTN3 aos indicadores de desempenho em atletas juvenis da natação brasileira especialistas em curtas distâncias

Abstract: Foi objetivo da pesquisa identificar a frequência genotípica da ACTN3 e associa-la ao índice técnico (IT) e ao status de elite em 98 atletas juvenis de natação (16,80 ± 0,63 anos) especialistas em curtas distâncias (≤ 200m). Um grupo controle (GC) com 101 escolares não-atletas (16,52 ± 0,94 anos) foi incluído nas comparações. Os grupos foram analisados sem divisão por sexo. Os atletas foram divididos pelas experiências competitivas em elite (internacionais, n = 15) e sub-elite (nacionais, n = 83). Não verifico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The majority of studies involving candidate polymorphisms related to swimming performance have given more attention to either ACTN3 or ACE polymorphisms [ 3 , 5 , 14 19 ]. In addition, other polymorphisms have also been investigated, such as the NOS3 genes (G894T and − 786T/C) [ 20 ], insulin-like growth factor ( IGF ) [ 21 ], myostatin ( MSTN ) [ 22 ], as well as interleukin-6 (IL6), MCT1, peroxisome proliferator-activated receptor alpha ( PPARA ), PPARG coactivator 1 alpha ( PPARGC1A ) and vascular endothelial growth factor receptor 2 ( VEGFR2 ) [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies involving candidate polymorphisms related to swimming performance have given more attention to either ACTN3 or ACE polymorphisms [ 3 , 5 , 14 19 ]. In addition, other polymorphisms have also been investigated, such as the NOS3 genes (G894T and − 786T/C) [ 20 ], insulin-like growth factor ( IGF ) [ 21 ], myostatin ( MSTN ) [ 22 ], as well as interleukin-6 (IL6), MCT1, peroxisome proliferator-activated receptor alpha ( PPARA ), PPARG coactivator 1 alpha ( PPARGC1A ) and vascular endothelial growth factor receptor 2 ( VEGFR2 ) [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ACTN3 polymorphism has been extensively studied and associated with elite athletic performance [ 35 , 36 ], including among swimming athletes [ 3 , 5 , 16 , 18 , 37 ]. The results of the present study showed that, regarding the ACTN3 gene, individuals with the XX genotype are 1.79 times more likely to belong to the athlete group when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the strength/power phenotype is associated with short-distance events, whereas the endurance phenotype is associated with long-distance events (3,5,6,9,10,17,23,26). However, there are few studies with young swimmers (18), especially experts in long-distance events. Likewise, no investigation has been geared to determine the distribution of these polymorphisms athletes expert in open water swimming (25).…”
Section: Introductionmentioning
confidence: 99%